Promising anticancer activities of Justicia simplex D. Don. in cellular and animal models. (6th March 2017) - Joseph, Litty; Aranjani, Jesil Mathew; Pai, K. Sreedhara Ranganath; Srinivasan, K.K.
Abstract: Ethnopharmacological relevance: Justicia simplex D. Don. belonging to the family of Acanthaceae has been traditionally used for treatment of rheumatism, inflammation and bronchitis. The plant is traditionally considered as an anticancer medicine and is used by healers of Karnataka to treat various types of cancers. Aim of the study: The present study aims at the elucidation of anticancer activity of various extracts of J. simplex, isolation of its active constituents and assessment of the role in growth inhibition and angiogenesis both in vitro and in vivo . Materials and methods: Extracts of J. simplex was evaluated for the in vitro cytotoxic effect by Brine Shrimp Lethality assay, Trypan Blue dye exclusion assay and antiproliferative assay. In vivo cytotoxicity of the extracts were determined by liquid tumor model in Swiss albino mice. Tumor prognosis, metastasis and angiogenesis were assessed by VEGF expression of the solid tumor. Phytochemical analysis afforded the isolation of a compound, the chemical structure of which was established using IR, NMR and TOF-MS spectral method. The compound was also evaluated for the growth inhibitory and angiogenic effects. Results and conclusion: The petroleum ether extract revealed potent anticancer activity in in vitro and in vivo studies. The anti-angiogenic effect is due to the down regulation of VEGF expression. The growth inhibitory assay revealed that the isolated compound namely triacontanoic ester of 5ʹʹ-hydroxyjustisolin is responsible for the anticancer activity. Graphical abstract: